Hegemony and Symbolic Resistance in Malaysia: A Study of Namewee’s Music - Tan, Chong Yew (Taylor's University, 2012)
Wee Meng Chee, better known as Namewee, is a controversial Malaysian rapper whose music has courted trouble with the Malaysian government. Although some people dismiss his songs as profane, this paper will highlight that Namewee’s music actually constitutes a critique of Malaysia’s social realities, and it challenges the BN ruling coalition’s political discourses, particularly UMNO’s ideology of Ketuanan Melayu (Malay hegemony). One recurring theme in Namewee’s songs is his frustration with policies that discriminate against Chinese Malaysians. To understand the significance of Namewee’s music, this paper refers to previous scholarly efforts in analysing the ways subordinate groups respond to domination and explores the potentials of rap music as a form of symbolic resistance against the dominant political discourse in Malaysia. Namewee’s works also stand out considering ‘protest songs’ are a rare genre in Malaysia.